Kinerja Keuangan Koperasi Syariah Sebelum Dan Sesudah Undang-Undang No. 1 Thn 2013. (Studi Pada Baitul Tamwil Muhammadiyah Di Jawa Tengah). - Usamah Said; Sobrotul Imtikhanah; Muhammad Khoirun (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2022)
This research aims to find out the effects of capital adequacy ratio, non performing financing, financing to deposit ratio, and operational costs and operating income on return on assets in BTM Central Java before and after Permenkop dan UKM no 16/2015 tentang usaha simpan pinjam syariah (KSPPS). The method that used is quantitative approach. The population in this study was 21 KSPPS BTM in Central Java. From the 21 population here were 14 KSPPS, the samples were used as 14 studies of BTM in Central Java. The analytical method is using multiple linear regression. Based on the results of the study concluded that CAR has a significant effect on ROA of KSPPS BTM before and after UU No. 1 of 2013. NPF has no significant effect on ROA on KSPPS BTM before UU No. 1 of 2013, but NPF have a significant and negative effect on ROA after UU No. 1 of 2013 on KSPPS BTM. FDR has no significant effect on ROA on KSPPS BTM before and after UU No. 1 of 2013. OCOI have a significant and negative effect on ROA on KSPPS BTM before and after UU No. 1 of 2013. BTM Central Java's ROA Before and After UU No. 1 of 2013 there is no difference. Keywords: Capital Adequacy Ratio, Non Performing Financing, Financing to Deposit Ratio, Operating Costs and Operating Income and Return On Asset